Statistical Analysis of the Performance of Modern Blog Platforms and Popular Blogs in the Uzbek Segment (Eurasian Journal of Media and Communications, 2025)
This scientific article is dedicated to the statistical analysis of the performance of modern blog platforms and their role in the information segment of Uzbekistan (the Uzbek segment). It analyzes the global and national development trends of blog platforms, and the main indicators of platform performance (number of users, content creation rate, level of interaction, and others) using statistical methods. A separate section of the article focuses on identifying the topics, audience, scope of influence, and success factors of popular blogs in the Uzbek segment. Based on the analysis results, conclusions are drawn regarding the development features of Uzbek blogging, current topics, and preferred platforms